2017
DOI: 10.1016/j.bjan.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Anestesia neuraxial em pacientes com esclerose múltipla – uma revisão sistemática

Abstract: Over a period of 65 years, our search resulted in 37 reports with a total of 231 patients. In 10 patients multiple sclerosis was worsened and nine multiple sclerosis or neuromyelitis optica was first diagnosed in a timely context with central neuraxial analgesia. None of the cases showed a clear relation between cause and effect. Current clinical evidence does not support the theory that central neuraxial analgesia negatively affects the course of multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Subarachnoid anesthesia has been postulated to exacerbate MS attacks due to the toxic effects of local anesthetics on demyelinated neurons. However, in a systematic review of neuraxial anesthesia in obstetric patients with MS, Bornemann-Cimenti et al 5 suggest that this mechanism of action is hypothetical and evidence is based on only a few case reports without a clear correlation between subarachnoid anesthesia and MS exacerbations. In addition, they report multiple incidences of spinal and epidural anesthesia in obstetric patients with MS with no negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Subarachnoid anesthesia has been postulated to exacerbate MS attacks due to the toxic effects of local anesthetics on demyelinated neurons. However, in a systematic review of neuraxial anesthesia in obstetric patients with MS, Bornemann-Cimenti et al 5 suggest that this mechanism of action is hypothetical and evidence is based on only a few case reports without a clear correlation between subarachnoid anesthesia and MS exacerbations. In addition, they report multiple incidences of spinal and epidural anesthesia in obstetric patients with MS with no negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Though MS is a distinct entity from NMO, the current literature has similarly shown no relationship between exacerbations of MS and neuraxial anesthesia. Two prospective studies evaluating the safety of epidural anesthesia in obstetric patients failed to show any negative outcomes [14]. A systematic review of 231 patients with MS also found no evidence that neuraxial anesthesia negatively affects the course of MS [14].…”
Section: Discussionmentioning
confidence: 99%
“…Two prospective studies evaluating the safety of epidural anesthesia in obstetric patients failed to show any negative outcomes [14]. A systematic review of 231 patients with MS also found no evidence that neuraxial anesthesia negatively affects the course of MS [14]. There are only case reports about spinal anesthesia and MS, but they also do not show a clear negative relationship.…”
Section: Discussionmentioning
confidence: 99%
“…There are no reported negative outcomes from the use of epidural, peridural, caudal, spinal, subarachnoid or intrathecal analgesia in MS [ 46 ]. Epidural analgesia can be safely used in women with MS who are giving birth [ 47 ].…”
Section: The Effect Of Ms On Obstetric Neonatal and Delivery Outcomementioning
confidence: 99%